2016
DOI: 10.1093/gerona/glw062
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Oxidative Burst by Primed Neutrophils in the Elderly Individuals Is Associated With Increased Levels of the CD16bright/CD62LdimImmunosuppressive Subset

Abstract: The aim of our study was to analyze polymorphonuclear neutrophil (PMN) functions in elderly individuals compared with those in healthy young participants, directly in whole blood to avoid issues with data interpretation related to cell isolation procedures. Despite the presence of increased circulating levels of proinflammatory cytokines, resting PMNs from the elderly individuals were not activated as shown by normal CD62L and CD11b expression at the PMN surface and normal constitutive reactive oxygen species … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(63 citation statements)
references
References 65 publications
1
56
0
4
Order By: Relevance
“…The increase in mature neutrophil numbers is most likely a result of glucocorticoid-induced demargination [39], as up to 50% of neutrophils are marginated in the endovascular lining in the noninjured state and can be very rapidly mobilised into the circulation to produce the neutrophilia of trauma. Compared to their CD16 BRIGHT CD62L BRIGHT counterparts, CD16 BRIGHT CD62L DIM neutrophils exhibit reduced ROS production, a trait shared by IGs, who also show reduced responsiveness to fMLF challenge [4042]. Thus, the heterogeneous neutrophil pool consisting of highly mature subsets and IGs that developed postinjury could be 1 factor underlying the altered neutrophil function we describe here.…”
Section: Discussionmentioning
confidence: 95%
“…The increase in mature neutrophil numbers is most likely a result of glucocorticoid-induced demargination [39], as up to 50% of neutrophils are marginated in the endovascular lining in the noninjured state and can be very rapidly mobilised into the circulation to produce the neutrophilia of trauma. Compared to their CD16 BRIGHT CD62L BRIGHT counterparts, CD16 BRIGHT CD62L DIM neutrophils exhibit reduced ROS production, a trait shared by IGs, who also show reduced responsiveness to fMLF challenge [4042]. Thus, the heterogeneous neutrophil pool consisting of highly mature subsets and IGs that developed postinjury could be 1 factor underlying the altered neutrophil function we describe here.…”
Section: Discussionmentioning
confidence: 95%
“…22 To investigate the senescent C-X-C chemokine receptor type 4 (CXCR4) high /CD62L low neutrophil subset, samples kept on ice were incubated for 45 minutes with phycoerythrin (PE)/cyanine 7 (Cy7)/antihuman CXCR4 (clone 12G5; Sony Biotech, San Jose, CA), PE/antihuman CD11b (clone ICRF44; BD Biosciences, San Jose, CA), and allophycocyanin (APC)/antihuman CD62L (BD Biosciences). 22 To investigate the senescent C-X-C chemokine receptor type 4 (CXCR4) high /CD62L low neutrophil subset, samples kept on ice were incubated for 45 minutes with phycoerythrin (PE)/cyanine 7 (Cy7)/antihuman CXCR4 (clone 12G5; Sony Biotech, San Jose, CA), PE/antihuman CD11b (clone ICRF44; BD Biosciences, San Jose, CA), and allophycocyanin (APC)/antihuman CD62L (BD Biosciences).…”
Section: Determination Of Surface Molecule Expression On Resting Neutmentioning
confidence: 99%
“…Differential phenotypic and functional features of neutrophils from AD-MCI and AD-D patients might be related to an imbalance between neutrophils subsets, that is, the overly active subset of senescent CXCR4 high neutrophils 40 and the immunosuppressive CD16 bright /CD62L dim subset of neutrophils exhibiting decreased proinflammatory properties 22,41,42 We observed an expansion of the senescent CXCR4 high /CD62L low subset of neutrophils in both groups of patients, and the percentage of neutrophils in the senescent subset was higher in AD-D than in AD-MCI patients (Fig 2A,C). Differential phenotypic and functional features of neutrophils from AD-MCI and AD-D patients might be related to an imbalance between neutrophils subsets, that is, the overly active subset of senescent CXCR4 high neutrophils 40 and the immunosuppressive CD16 bright /CD62L dim subset of neutrophils exhibiting decreased proinflammatory properties 22,41,42 We observed an expansion of the senescent CXCR4 high /CD62L low subset of neutrophils in both groups of patients, and the percentage of neutrophils in the senescent subset was higher in AD-D than in AD-MCI patients (Fig 2A,C).…”
Section: Homeostasis Of the Circulating Neutrophils Differed For Neutmentioning
confidence: 99%
“…In contrast, CD16 high CD62L dim neutrophils from elderly patients had a lower phagocytic index and exhibited a lower oxidative burst compared with the mature neutrophil subset. 6 However, these subsets were Since Pillay et al identified CD16 high CD62L dim neutrophils, this subset has mostly been studied in cancer. CD16 high CD62L dim neutrophils were prone to migrate into the tumor in patients with head and neck squamous cell carcinoma (HNSCC), due to increased CD11b and CD18 expression, and inhibited migration and proliferation and induced apoptosis of FaDu cancer cells.…”
Section: Subsetting Reveals Cd16 High Cd62l Dim Neutrophils In Chronimentioning
confidence: 99%